Hepatitis A Virus Infections Among Men Who Have Sex with Men — Eight U.S. States, 2017–2018 - Foster, Monique A.; Hofmeister, Megan G.; Albertson, Justin P.; Brown, Kerri B.; Burakoff, Alexis W.; Gandhi, Ami P.; Glenn-Finer, Rosie E.; Gounder, Prabhu; Ho, Po-Yi; Kavanaugh, Tracy; Latash, Julia; Lewis, Rebecca L.; et al. (MMWR. Morbidity and mortality weekly report, 2021)
During 1995-2011, the overall incidence of hepatitis A decreased by 95% in the United States from 12 cases per 100,000 population during 1995 to 0.4 cases per 100,000 population during 2011, and then plateaued during 2012─2015. The incidence increased by 294% during 2016-2018 compared with the incidence during 2013-2015, with most cases occurring among populations at high risk for hepatitis A infection, including persons who use illicit drugs (injection and noninjection), persons who experience homelessness, and men who have sex with men (MSM) (1-3). Previous outbreaks among persons who use illicit drugs and MSM led to recommendations issued in 1996 by the Advisory Committee on Immunization Practices (ACIP) for routine hepatitis A vaccination of persons in these populations (4). Despite these long-standing recommendations, vaccination coverage rates among MSM remain low (5). In 2017, the New York City Department of Health and Mental Hygiene contacted CDC after public health officials noted an increase in hepatitis A infections among MSM. Laboratory testing* of clinical specimens identified strains of the hepatitis A virus (HAV) that subsequently matched strains recovered from MSM in other states. During January 1, 2017-October 31, 2018, CDC received reports of 260 cases of hepatitis A among MSM from health departments in eight states, a substantial increase from the 16 cases reported from all 50 states during 2013-2015. Forty-eight percent (124 of 258) of MSM patients were hospitalized for a median of 3 days. No deaths were reported. In response to these cases, CDC supported state and local health departments with public health intervention efforts to decrease HAV transmission among MSM populations. These efforts included organizing multistate calls among health departments to share information, providing guidance on developing targeted outreach and managing supplies for vaccine campaigns, and conducting laboratory testing of clinical specimens. Targeted outreach for MSM to increase awareness about hepatitis A infection and improve access to vaccination services, such as providing convenient locations for vaccination, are needed to prevent outbreaks among MSM.During 1995-2011, the overall incidence of hepatitis A decreased by 95% in the United States from 12 cases per 100,000 population during 1995 to 0.4 cases per 100,000 population during 2011, and then plateaued during 2012─2015. The incidence increased by 294% during 2016-2018 compared with the incidence during 2013-2015, with most cases occurring among populations at high risk for hepatitis A infection, including persons who use illicit drugs (injection and noninjection), persons who experience homelessness, and men who have sex with men (MSM) (1-3). Previous outbreaks among persons who use illicit drugs and MSM led to recommendations issued in 1996 by the Advisory Committee on Immunization Practices (ACIP) for routine hepatitis A vaccination of persons in these populations (4). Despite these long-standing recommendations, vaccination coverage rates among MSM remain low (5). In 2017, the New York City Department of Health and Mental Hygiene contacted CDC after public health officials noted an increase in hepatitis A infections among MSM. Laboratory testing* of clinical specimens identified strains of the hepatitis A virus (HAV) that subsequently matched strains recovered from MSM in other states. During January 1, 2017-October 31, 2018, CDC received reports of 260 cases of hepatitis A among MSM from health departments in eight states, a substantial increase from the 16 cases reported from all 50 states during 2013-2015. Forty-eight percent (124 of 258) of MSM patients were hospitalized for a median of 3 days. No deaths were reported. In response to these cases, CDC supported state and local health departments with public health intervention efforts to decrease HAV transmission among MSM populations. These efforts included organizing multistate calls among health departments to share information, providing guidance on developing targeted outreach and managing supplies for vaccine campaigns, and conducting laboratory testing of clinical specimens. Targeted outreach for MSM to increase awareness about hepatitis A infection and improve access to vaccination services, such as providing convenient locations for vaccination, are needed to prevent outbreaks among MSM.